Limiting potential COVID-19 contagion in squatting public toilets - Li Pan; Shuang-Lan Chen; Yi-Sha Guo; Yu-Xiang Du; Xiao-Di Wu; Alice Y. M. Jones; Jia Han (World Scientific Publishing, 2021)
Background: Since the outbreak of the SARS-CoV-2 virus in December 2019, the COVID-19 pandemic continues to threaten global stability. Transmission of SARS-CoV-2 is mostly by respiratory droplets and direct contact but viral RNA fragments have also been detected in the faecal waste of patients with COVID-19. Cleanliness and effective sanitation of public toilets is a concern, as flushing the toilet is potentially an aerosol generating procedure. When the toilets are of the squatting type and without a cover, there exists a risk of viral contamination through the splashing of toilet water and aerosol generation. Objective: This study aims to determine whether the cleanliness of public toilets was a concern to the general population during the COVID-19 pandemic, and whether a squatting toilet was preferred to a seated design. Methods: A questionnaire was designed and posted on "WeChat" contact groups of the investigators. Results: The survey showed that 91% of participants preferred squatting toilets, but that 72% were apprehensive of personal contamination when using public toilets. Over 63% of the respondents had encountered an incidence of water splash and would prefer public toilets to be covered during flushing and 83% of these respondents preferred a foot-controlled device. Conclusion: This survey suggests that consideration should be given to the installation of a simple foot-controlled device to cover public squatting toilets to help restrict potential COVID-19 contamination and to meet hygienic expectations of the public.